2009
DOI: 10.1007/s12562-009-0138-5
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and probiotic effects of lactic acid bacteria in the gut of the abalone Haliotis gigantea

Abstract: Strains of lactic acid bacteria (LAB) were isolated from several different sources and evaluated in vitro for potential probiotic effects in abalones. Two isolates (Lactobacillus sp. strain a3 and Enterococcus sp. strain s6) were highly resistant to bile salt and/or gastric juice and inhibited the growth of three abalone pathogens (Listonella anguillarum, Vibrio harveyi, and V. carchariae). Each of the LAB isolates was used to supplement diet of the abalone Haliotis gigantea for a period of 3 weeks. One group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Furthermore, hydrolysis products from enzymatic polysaccharide digestion, such as mannooligosaccharides from manna, have shown prebiotic microflora modulation in humans (Dhawan and Kaur, 2007). Probiotic manipulation of the gut microflora in abalone has shown promising results for animal health, nutritional physiology and growth (Iehata et al, 2009(Iehata et al, , 2010Macey and Coyne, 2005;Silva-Aciares et al, 2011;Ten Doeschate and Coyne, 2008). Of particular interest in these studies are the elevated digestive enzyme activities associated with the administration of probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hydrolysis products from enzymatic polysaccharide digestion, such as mannooligosaccharides from manna, have shown prebiotic microflora modulation in humans (Dhawan and Kaur, 2007). Probiotic manipulation of the gut microflora in abalone has shown promising results for animal health, nutritional physiology and growth (Iehata et al, 2009(Iehata et al, , 2010Macey and Coyne, 2005;Silva-Aciares et al, 2011;Ten Doeschate and Coyne, 2008). Of particular interest in these studies are the elevated digestive enzyme activities associated with the administration of probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The broths were inoculated from a colony and incubated at 22°C for 3 h. Survival was determined by comparing the viable plate count after 3 h with that at 0 h (incubated at pH 6.5) (Iehata et al 2009). …”
Section: Screening the Isolates For Hydrolysis Of Nutrientsmentioning
confidence: 99%
“…Subsequently, ten Doeschate & Coyne (2008) demonstrated that H. midae exhibited an increased growth rate when fed a kelp diet supplemented with Pseudoalteromonas sp., and they recorded a significantly higher alginate lyase activity (presumably assisting the digestion of the kelp) in the digestive tract of those animals fed the supplemented diet. In addition, Iehata et al (2009) isolated lactic acid bacteria from a range of sources and, based on in vitro tests for inhibition of pathogens and resistance to bile acids and gastric juice, selected a Lactobacillus sp. and an Enterococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…While the level of probiotic organisms incorporated into supplemented feeds varies, most aquaculture-related studies supply a minimum probiotic titre of 10 6 cfu g −1 (Al-Dohail et al, 2009;Castex et al, 2008Castex et al, , 2009Iehata et al, 2009;Li et al, 2009;Macey and Coyne, 2005;Merrifield et al, 2010;Rengpipat et al, 1998;Sáenz de Rodrigáñez et al, 2009;Sharifuzzaman and Austin, 2009;ten Doeschate and Coyne, 2008). Consequently, the abalone in this investigation were supplied with ABFEED ® S34 supplemented with at least 1 × 10 6 cfu g −1 of feed over the course of the growth trial.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic supplementation can result in a range of beneficial effects, including enhanced health, immunity, survival and growth in a wide variety of cultured aquatic organisms. Although there have been many studies investigating probiotics for cultured finfish and crustaceans (Allameh et al, 2012;Andani et al, 2012;Balasundaram et al, 2012;Decamp et al, 2008;Keysami et al, 2012;Tapia-Paniagua et al, 2010), there have been relatively few reports describing probiotics for cultured molluscs such as abalone (Iehata et al, 2009(Iehata et al, , 2010Macey and Coyne, 2005;Silva-Aciares et al, 2011;ten Doeschate and Coyne, 2008).…”
Section: Introductionmentioning
confidence: 99%